Concealment and Revelation: Forensic Analysis in Homicide Investigations - A Case Series (Journal of Forensic Medicine & Toxicology, 2026)
Concealed homicides present major challenges to forensic investigation by obscuring evidence, complicating identifica tion, and hindering the determination of cause and manner of death. This study analyses six cases of concealed homicide  examined between May 2023 and May 2025 at a tertiary care hospital mortuary in South India. The victims, aged 21–31  years, included five males and one female. Alcohol was detected in five cases, indicating its contributory role in violent  behaviour. Causes of death included cranio-cerebral injuries in three cases, cut-throat injury and ligature strangulation  each in one instance, and one undetermined due to advanced decomposition. Concealment methods included burial  (three cases), staged drowning (one case), post-mortem suspension mimicking suicide (one case), and dismemberment  with submersion (one case), corresponding to Grades 1–3 of Schneikert’s concealment classification. Stages of decom position ranged from early putrefaction to partial skeletonisation. Identification was established through tattoos and  clothing in four cases and confirmed by DNA profiling in all. This case series highlights the crucial role of comprehen sive forensic examination, toxicological analysis, and DNA profiling in uncovering concealed homicides and ensuring  accountability under the law.
Keywords: Concealment; Homicide; perpetrator; Forensic medicine; Autopsy